The impact of covid-19 pandemic on the housing sector from the perspective of home ownership affordability - Rameli, Norizan; Bukhari, Norshuhada; Ani, Fauziah; Saleh, Nor Shela; Johar, Siti Sarawati; Ramli, Fariha (GADING Journal for the Social Sciences, 2023)
The Covid-19 pandemic has increasingly affect the lives of people and together with it, the economic sector. The spread disrupts the country’s economic ecosystem, including the housing sector. Though debates on the impact of Covid-19 towards the economy are abundant, the discussions of the impacts of Covid-19 towards the housing sector from the perspective of home ownership affordability are still lacking. Therefore, this article will study the impact of the pandemic on home ownership affordability. Discussions involved the instability of housing affordability in terms of household income, type and sector of employment, household expenditure, followed by the housing ownership and rental sector which include affordable housing, home ownership and rental in the pandemic phase and potential housing rental sector. This article unlocks a debate on the challenges and sustainability aspects of home ownership affordability for the endemic phase.